No Pharmacokinetic Interactions Between Elbasvir or Grazoprevir and Methadone in Participants Receiving Maintenance Opioid Agonist Therapy. Issue 6 (24th July 2018) - Feng, Hwa‐Ping; Guo, Zifang; Caro, Luzelena; Marshall, William L.; Liu, Fang; Panebianco, Deborah; Vaddady, Pavan; Reitmann, Christina; Jumes, Patricia; Wolford, Dennis; Fraser, Iain; Valesky, Robert; et al.
Abstract: We conducted two phase I trials to evaluate the pharmacokinetic interactions between elbasvir (EBR), grazoprevir (GZR), and methadone (MK‐8742‐P010 and MK‐5172‐P030) in non‐hepatitis C virus (HCV)‐infected participants on methadone maintenance therapy. Coadministration of EBR or GZR with methadone had no clinically meaningful effect on EBR, GZR, or methadone pharmacokinetics. The geometric mean ratios (GMRs) for R‐ and S‐methadone AUC0‐24 were 1.03 (90% confidence interval (CI), 0.92 –1.15) and 1.09 (90% CI, 0.94 –1.26) in the presence/absence of EBR; and 1.09 (90% CI, 1.02 –1.17) and 1.23 (90% CI, 1.12 –1.35) in the presence/absence of GZR. The GMRs for EBR and GZR AUC0‐24 in participants receiving methadone relative to a healthy historical cohort not receiving methadone were 1.20 (90% CI, 0.94 –1.53) and 1.03 (90% CI, 0.76 –1.41), respectively. These results indicate that no dose adjustment is required for individuals with HCV infection receiving stable methadone therapy and the EBR/GZR fixed‐dose regimen .